Subdural Effusion Complicating Purulent Meningitis - Taslim S. Sutomenggolo; Sofjan Ismael; Harry Ch. Hardjatno; S. M. Lumbantobing (Paediatrica Indonesiana, 1974)
The purpose of this paper is toevaluate the incidence, sex, age, nut-ritional condition, finding the effusi-on, mortality and, clinical signs andsymptoms which can support the di-agnosis of subdural effusion.